Assessing the transportation of liquid fuels in South Africa using multi-criteria decision analysis: a conceptual framework and case study - Coelho, Marco (Department of Civil Engineering, 2017)
With the recent unprecedented growth of many African economies, infrastructure investment has been flooding into the continent. Two key areas experiencing large growth in infrastructure development are the transport and energy sectors. This trend also continues to hold true in the South African development framework. The theme of this thesis encompasses both subjects of energy and transportation infrastructure which feature prominently in the countries development plans. When energy is discussed in South Africa, it is usually in the context of power generation and electricity distribution. This study focuses on another key component of the energy sector in the form of liquid fuel. Most of this energy is consumed for transportation purposes. The energy consumption of the transport sector in South Africa is large, totalling around 28% of Total Final Consumption (TFC) in the national energy balances. The bulk of this energy demand (97%) is in the form of liquid fuels, accounting for 84% of the national liquid fuel demand. This thesis focusses on the investigation of a Multi Criteria Decision Analysis (MCDA) model, which can be used to aid decision makers in the planning and assessment of liquid fuel transportation projects. A key feature of this thesis is the incorporation of a stochastic analysis in the MCDA model. There are two key motivations for assimilating a stochastic analysis in this investigation. The first one is the evaluation of incorporating such an analysis in an MCDA, as opposed to a more traditional sensitivity analysis. The second motivation is to assess the value of employing stochastic analysis as an input method for analysing a decision problem, where comprehensive field data can be substituted for a relevant range of simulated data. This thesis proposes a model which integrates the MCDA and stochastic analysis in the hope that it would provide a faster and more cost effective alternative for assessing certain liquid fuel transportation problems.